Gravity Probe B cryogenic payload. (17th November 2015) - Everitt, C W F; Parmley, R; Taber, M; Bencze, W; Burns, K; Frank, D; Kolodziejczak, J; Mester, J; Muhlfelder, B; Murray, D; Reynolds, G; Till, W; et al.
Abstract: This paper gives a detailed account of the Gravity Probe B cryogenic payload comprised of a unique Dewar and Probe. The design, fabrication, assembly, and ground and on-orbit performance will be discussed, culminating in a 17 month 9 day on-orbit liquid helium lifetime.